Invisible sprawl: land, money and politics at the rural-urban interface in Kenya. - Bon, Bérénice (Taylor & Francis, 2021)
Policy guidelines for controlling urban growth have, since the end of the late 2000s, been imposed on sub-Saharan Africa in international and national agendas. Like many other cities in sub-Saharan Africa, Nairobi is experiencing rapid demographic and spatial growth. Debates on urban sprawl are primarily concerned with the question of density, with attention to the extension of buildings and institutional real estate markets. This article focuses on what happens even before construction takes place, sometimes years earlier on the outskirts of urban agglomerations and on new urbanisation fronts far from urban centralities. Access to land is central to carrying out large metropolitan projects and supporting the accumulation logics of real estate firms, financial investors and individual entrepreneurs. It is also central in the transformations of local economies in contexts of a restructuring of agrarian capitalism. We intend to bring to light these trajectories of land capitalisation by analysing the practices and anticipation of land investors with diverse economic and informational resources, the circulation of financial capital and the resulting urban configurations.
Keywords: Ländlicher Raum; Baulandbeschaffung; Bodenmarkt; Bodenwert; Zersiedelung; Sprawl; Landnutzung; Bodenpolitik; Raumordnungspolitik